Brief Reviews of Books and Products: A History of Scientific Journals: Publishing at the Royal Society, 1665-2015 - Tomasz Mrozewski (Journal of Librarianship and Scholarly Communication, 2023)
A review of A History of Scientific Journals: Publishing at the Royal Society, 1665-2015